PEMANFAATAN KEKAYAAN ALAM DAN HASIL PERTANIAN SEBAGAI MODAL PENGEMBANGAN AGROWISATA DAERAH - Abdurrahman Kader; Salma Soleman (LEMBAGA PENELITIAN PUBLIKASI DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2020)
The purpose of this study is to describe the use of natural resources and agricultural products as capital and resources in the development of regional agrotourism. This research uses a qualitative descriptive approach, and the data analysis technique used is an interactive model. Kalaodi agrotourism area there are various wealth of attractions. Kalaodi agrotourism wealth, there are natural attractions, in the form of a beautiful environment, beautiful scenery and cool air. In the natural environment of Kalaodi there are a variety of plants from agriculture and plantations such as cloves, nutmeg, durian, melinjo, cinnamon, bamboo and others. In Kalaodi village there is also a home industry that produces melinjo crepe, melinjo chips, nutmeg syrup, nutmeg candied, jam nutmeg, and souvenirs.